(untitled) (Universal International Scientific Journal, 2026)
This thesis analyzes the psychological causes and consequences of anxiety in preschool children, as well as effective means of reducing them. The thesis examines in detail the methods of increasing children’s emotional stability through music therapy, the psychocorrective effect of rhythmic and creative activities, as well as the influence of the family environment on the psyche of children.